The North-South divide in Europe: an economic anomaly or more of an existential question? - Saltik, Serkan (Universitätsbibliothek Heidelberg, 2015)
The EU’s protracted debt crisis has been addressing an obvious split between its northern and southern members. Granted that contractions over the last decade have taken their toll in the goods, services and financial markets of the latter group far more heavily than in those of the former, the economic implications of the Greek bailout negotiations lately are overshadowed by deep-seated fissures at the public level. As the findings of this comparative study substantiate them, there exist currently significant signs of resentment between citizens of the EU’s northern and southern Member States.